2017
DOI: 10.3892/mco.2017.1367
|View full text |Cite
|
Sign up to set email alerts
|

Collagen gel droplet-embedded culture drug sensitivity testing in hard palate cancer-predicted antitumor efficacy of cetuximab: A case report

Abstract: Abstract.In vitro anticancer drug sensitivity assessments have been performed for various types of cancer, and an association with clinical response has been observed. The collagen gel droplet-embedded culture drug sensitivity test (CD-DST) is an in vitro anticancer drug sensitivity test that has recently reported to be useful in oral squamous cell carcinoma (OSCC). CD-DST allows for the analysis of a smaller number of cells compared with other anticancer drug sensitivity tests. The present study reported a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…CD-DST, collagen gel droplet-embedded culture drug sensitivity test; CDDP, cisplatin; 5-FU, 5-fluorouracil; PF, CDDP+5-FU; T/C, total colony of the treated cells/total colony of the untreated cells. and compared the results to those of sensitivity testing of PF + cetuximab and its clinical efficacy (20). In the same study, the T/C% of the CD-DST method was found to represent high sensitivity at 32.4%, and the clinical efficacy of PF + cetuximab was consistent with the partial response (20).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…CD-DST, collagen gel droplet-embedded culture drug sensitivity test; CDDP, cisplatin; 5-FU, 5-fluorouracil; PF, CDDP+5-FU; T/C, total colony of the treated cells/total colony of the untreated cells. and compared the results to those of sensitivity testing of PF + cetuximab and its clinical efficacy (20). In the same study, the T/C% of the CD-DST method was found to represent high sensitivity at 32.4%, and the clinical efficacy of PF + cetuximab was consistent with the partial response (20).…”
Section: Discussionmentioning
confidence: 91%
“…and compared the results to those of sensitivity testing of PF + cetuximab and its clinical efficacy (20). In the same study, the T/C% of the CD-DST method was found to represent high sensitivity at 32.4%, and the clinical efficacy of PF + cetuximab was consistent with the partial response (20). The reported T/C% is 32.4%, which is less than 40% of the cut-off value we determined in the present study, and can be considered to represent high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…This method has advantages in that it allows testing using smaller quantities of cells compared with conventional assays. Furthermore, it eliminates the effects of fibroblasts that can adulterate samples at the time of harvesting and allows the evaluation of physiological drug concentrations [13][14][15][16] . In addition, the CD-DST method can be evaluated by combining multiple anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…The collagen gel droplet-embedded culture drug sensitivity test (CD-DST), which was developed by Kobayashi et al [11], is an anticancer drug sensitivity test that combines three-dimensional (3D) microcarrier cell culture with serum-free medium and image-based colorimetric analysis [11]. This method has demonstrated high success rates for a wide range of diseases, including OSCC, by overcoming many the limitations of conven-tional chemosensitivity tests [12][13][14][15]. Because CD-DST uses a micro-3D culture, it can be used to evaluate OSCC and other cancers that have low tumor volume.…”
Section: Introductionmentioning
confidence: 99%